2018
DOI: 10.1159/000490834
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of MiR-20a Enhances Sensitivity of Colorectal Cancer Cells to Cisplatin by Increasing ASK1 Expression

Abstract: Background/Aims: Platinum-based chemotherapy is one of the most important strategies for treatment of colorectal cancer. To improve the therapeutic efficiency, adjuvant drugs were sought to sensitize colorectal cancer cells to platinum-based agents such as cisplatin. As previous research has shown that miRNAs are associated with chemosensitivity, we aimed to alter miRNA regulation in colorectal cancer cells to increase their chemosensitivity. Methods: MTT assays were performed to determine the viability of HT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Recent studies have demonstrated that formation of cisplatin resistance is partially induced by dysregulation of miRNAs in cancers including NSCLC. [24][25][26] MiRNAs have been considered as potential targets for improving the cisplatin-based treatment. Among these cancer-related miRNAs, miR-26b acts as a tumor suppressor and is always downregulated in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that formation of cisplatin resistance is partially induced by dysregulation of miRNAs in cancers including NSCLC. [24][25][26] MiRNAs have been considered as potential targets for improving the cisplatin-based treatment. Among these cancer-related miRNAs, miR-26b acts as a tumor suppressor and is always downregulated in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miRNAs are associated with the expression of a number of target genes that are related to chemosensitivity or the sensitivity of drugs to cancer cells (110). Therefore, identifying an indicator to monitor CRC chemotherapy is important and recent studies have indicated that miR-20a can be used as a monitoring indicator for chemotherapy (111,112). miR-20a is differentially expressed before and after chemotherapy.…”
Section: Mir-20a May Be Used As a Monitoring Indicator During Chemothmentioning
confidence: 99%
“…However, the chemotherapy resistance of CRC cells is challenge in the treatment of patients with CRC (119). Studies have indicated that miR-20a induces cisplatin resistance in numerous cancers, potentially including in CRC (55,57,111,112). The miR-20a inhibitor can sensitize cisplatin-induced CRC cytotoxicity via the reactive oxygen species (ROS) pathway.…”
Section: Mir-20a May Be Used As a Monitoring Indicator During Chemothmentioning
confidence: 99%
See 2 more Smart Citations